„A nő rejtélye”: Olvasás és ismétlés Kemény Zsigmond Ködképek a kedély láthatárán című regényében - Somogyi, Gyula (Studia Litteraria, 2014)
The essay reads Zsigmond Kemény’s Ködképek a kedély láthatárán through theoretical insights provided by psychoanalysis, gender studies and deconstruction. The first part of the text is devoted to an analysis of narrative roles from the perspective of political power; observing how the friendship of Várhelyi and Cecil - the protagonists of the story -, seems to escape such power structures; at the same time, it represents the woman as an enigma and metaphorizes her soul as a fragment. The second part of the essay rereads Cecil’s tale of Ameline with the use of conventions and textual constructions found in (female) gothic genre concluding with some thoughts about how these two seemingly diverging sets of questions are intimately related to each other.